Analisis Pengaruh Lingkungan Kerja Non Fisik, Besaran Gaji, Beban Kerja dan Kepuasan Kerja Terhadap Turnover Intention - Jecelyn, Jecelyn; Hamzah, Zulfadli (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to analyze the influence of the non-physical work environment, salary, workload and job satisfaction on turnover intention at PT Rimba Prima Mas both partially and simultaneously. This study uses multiple linear regression analysis using the SPSS version 21 application, with a total sample of 80 employees at PT Rimba Prima Mas. The results showed that only the workload variable had a significant effect on turnover intention at PT Rimba Prima Mas, while the non-physical work environment variables, the amount of salary, and had no effect on turnover intention at PT Rimba Prima Mas. Non-physical work environment variables, salary, workload and job satisfaction have contributed 73.1% to the turnover intention variable, although there are still 26.9% influence on other factors not included in the study.